Pelatihan Peningkatan KeterampilanMatematika dan Etika Kewarganegaraan dalamMempersiapkan Lulusan Sarjana - Kusumawati, Intan; Putri, Prihastini Oktasari; Paiman (CV. Kurnia Grup, 2025)
Given the challenges of the working world and the demands of professionalism as prospective educators, students are required not only to master academic competencies, but also to possess logical thinking skills and moral and ethical integrity as citizens. This community service activity aims to improve basic mathematical skills and an understanding of civic ethics for prospective undergraduate students of the Faculty of Teacher Training and Education (FKIP), Cokroaminoto University, Yogyakarta. This training method provides participants with intensive material in two main areas: strengthening basic mathematical concepts and applying them, and instilling civic ethics values in the context of national and state life. The training method is carried out in a participatory manner through an andragogical approach, group discussions, case studies, and contextual practice questions. Evaluation of the activity shows that this training has a positive impact on increasing student self-confidence, strengthening their numerical skills, and fostering ethical awareness in decision-making as prospective educators. The results of this training encourage students to be better prepared to face the world of work and have social sensitivity as part of their civic responsibilities. This program is expected to be sustainable and become a model for developing transdisciplinary skills in preparing FKIP graduates who excel academically, ethically, and professionally.